2011
DOI: 10.1002/poc.1881
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical prediction on the ground‐state complexes bound by metal ions to thymine base isomers

Abstract: Stability orderings of 150 stable complexes formed by metal ions (Na+, K+, Ca2+, Mg2+, and Zn2+) and 13 stable thymine tautomers in both solvent and gas phases are obtained, and the optimal binding site for a metal ion in a specific thymine tautomer is identified. Results indicate that the complex with the canonical thymine tautomer (T1) is more stable than those with the rare ones, and the monodentate complex M–T1o4(o2) are their ground‐state form in the solvent phase. The ground‐state thymine complexes bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In agreement with previous studies, 23,38 the most stable complexes of thymine tautomers with metal ions are found for thy1, where the cation interacts with the O10 atom of the carbonyl group (M + ⋯O10). The decrease of thymine complexes stability up to E rel = 10 kcal mol −1 (Table S6 ‡) occurs in the following sequence: M + ⋯N3,O8 of thy3, M + ⋯O8 of thy1 and M + ⋯O10 of thy2.…”
Section: Interactions With Metal Cations (M + )supporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous studies, 23,38 the most stable complexes of thymine tautomers with metal ions are found for thy1, where the cation interacts with the O10 atom of the carbonyl group (M + ⋯O10). The decrease of thymine complexes stability up to E rel = 10 kcal mol −1 (Table S6 ‡) occurs in the following sequence: M + ⋯N3,O8 of thy3, M + ⋯O8 of thy1 and M + ⋯O10 of thy2.…”
Section: Interactions With Metal Cations (M + )supporting
confidence: 92%
“…Thymine is a six-membered heterocyclic molecule which can exist in the form of 13 tautomers/rotamers. The 1H,3Hdiketo tautomer, which contains two CvO groups and two N-H groups constituting inherent parts of the ring, is the most stable in the gas phase, solution and the solid state 19,20 which was confirmed by a series of theoretical [21][22][23] and experimental † Dedicated to our friend, Professor Jacek Lipkowski of Guelph University, on the occasion of his 70 th birthday.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…For divalent cations, it has been experimentally shown that the coordination at the N7 position of adenine is preferred, whereas for Ag + , the coordination occurs at N3 and N7 of adenine . The bases thymine and uracil bind the metal cations at O4 atom . For guanine and cytosine, the coordination with cation is bifurcated, that is, the metal cation is bound to the N7 and O6 atoms of guanine and the N3 and O2 atoms of cytosine, respectively.…”
Section: Introductionmentioning
confidence: 99%